(untitled) (Community Based Medical Journal, 2022)
Chronic neuropathic pain disorders represent a common long-term disability globally. Its treatment has limited success because of its poorly understood mechanisms. Moreover, the effectiveness of neuropathic pain management regimens and procedures have been difficult to determine to date, due to the subjectivity related to pain perception, and a lack of standardized assessment of neuropathic pain. However, one of the most effective and popular management strategies of chronic neuropathic pain in recent times is spinal cord stimulation (SCS), a form of neuromodulation. This review aims to understand which substances inside the human body increase and decrease with increasing neuropathic pain. Through identifying those biomarkers and finding correlations between neuropathic pain and those components, we would like to apply our knowledge to develop a biomarker profile which will ultimately help to see prognosis or predict success of spinal cord stimulation therapy in patients suffering from chronic neuropathic pain. CBMJ 2021 January: vol. 10 no. 02 P: 118-122